Guerra e Fome na Somália - Penna Filho, Pio (Meridiano 47 - Journal of Global Studies, 2017)
This article discusses the situation in Somalia, especially the recent food crisis, from the country’s recent history, especially with the disintegration of the state with the fall of Siad Barre in the early 1990s. It argues that only you can forward the issue of hunger when the state is rebuilt and restored peace.